A Performance Study of Home-Made Co-Immobilized Lipase from Mucor miehei in Polyurethane Foam on The Hydrolysis of Coconut Oil to Fatty Acid - Dwina Moentamaria; Maktum Muharja; Tri Widjaja; Arief Widjaja (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
Bio‐based fatty acids (FAs) produced through hydrolysis of natural oils and fats are promising chemical feedstocks for increasing the economic value of renewable raw materials. In this work, lecithin, gelatin, PEG, and MgCl2 were employed as the co-immobilized material of crude lipase Mucor miehei immobilization on the polyurethane foam (PUF) matrix for hydrolysis of coconut oil to Free Fatty Acid (FFA). The unconventional immobilized technique was used through cross-linking and covalent bond. Single factor analysis and response surface method were utilized to determine the optimum conditions of the hydrolysis reaction. After optimization, co-immobilized lipase was examined for storage stability at a temperature of 4°C and reusability performance. The optimum conditions for coconut oil hydrolysis were obtained on the co-immobilized-PUF ratio, water-oil ratio, and reaction time of 20.17 w/w, 4.45 w/w, and 20 h, respectively. Under these conditions, the acid value as lauric acid enhanced 573% to 3.21 mg KOH/g oil. Storage stability attained through remaining activity on free lipase, PUF-lipase, PUF-co-immobilized-lipase were 9.89%, 42.3%, and 91.88%, respectively. In this study, the application of PUF-co-immobilized lipase in hydrolysis reactions can be reused up to 5 times. Characteristics of the addition of co-immobilized lipase have been analyzed using Fourier Transform Infra Red (FTIR) and Scanning Electron Microscope (SEM), showing the presence of functional groups binding and the changes in the surface matrix structure.